SOIL MANAGEMENT SYSTEMS AND WATER RELATIONS ON THE SOYBEAN CROP PRODUCTIVITY, IN THE REGION OF PONTA GROSSA, STATE OF PARANA, BRAZIL - ARAUJO, Marla Alessandra; SOUZA, Jorge Luiz Moretti; BRONDANI, Gilvano Ebling; PAULETTI, Volnei (Scientia Agraria, 2009)
This study aimed to evaluate the influence of four management systems and soil water relations on the soybean crop productivity. The soil is a Typic Hapludox and it is located in Ponta Grossa region, State of Parana, Brazil. Soybean crop productivity (11 crop seasons) and climate data were made available by ABC Foundation and SIMEPAR, respectively. The management systems did not differ significantly in relation to the productivity. However, because of the water deficit occurrence in the most critical phenological stages, the crop seasons 1998/99, 2001/02 and 2004/05 produced 347.5 kg ha-1, 462.0 kg ha-1 and 358.3 kg ha-1 less than the medium productivity, respectively. The soybean crop productivity of consecutive years, in the crops rotation cycle, presented 10.31% of reduction medium in the second crop seasons compared to the first ones.